The Effect of Giving Gotu Kola Tea and Green Tea on Hypertension Patients in the “Imayah” Elderly Posyandu, Betro Village in Sidoarjo - Mayandari, Wahidah Romadloni; Mubarokah, Lailatul; Astutik, Fifit Eka Furi; Munaa, Nihayatul (Jurnal EduHealth, 2022)
Hypertension is an increase at the systolic and dastolic blood pressure the exceeds the threshold. This study was Centella Asiatica L and Camellia Sinensis to contain several compounds, that can work as antihypertensives including ACE inhibitors. So, that can lower blood pressure. The purpose study to determine the effect Centella Asiatica L and Camellia Sinensis on systolic and diastolic blood pressure in hypertensive patient in Betro Village. The method is a control group design. This research use a purposive sampling technique with 40 people aged 60-80 years. The analyze data is a T-test analysis pair test and Independent T. The result of this study is an examination on systolic and diastolic blood pressure were mostly decreased. There was a significant difference in blood pressure before and after being given Centella Asiatica L, with a value of p=0.064 and p=0.003. And here was a significant difference in blood pressure before and after being given Camellia Sinensis, with a value of p=0.005 and p=0.011. The conclusion, there is an effect of two tea on systolic and diastolic blood pressure in resondent at the Posyandu elderly Ismayah Betro Village.